Biological effects of Ni(II) on monocytes and macrophages in normal and hyperglycemic environments. Issue 9 (14th May 2018) - Chana, Monica; Lewis, Jill B.; Davis, Ryan; Elam, Yolanda; Hobbs, David; Lockwood, Petra E.; Wataha, John C.; Messer, Regina L.
Abstract: Corrosion and release of nickel ions from biomedical alloys are well documented, but little is still known about the effects of released nickel ions on cellular function with recurrent inflammatory challenges. Evidence suggests Ni(II) ions amplify LPS‐induced secretion of several pro‐inflammatory cytokines from monocytes. Exacerbating the inflammatory response, hyperglycemic conditions also affect monocytic function. This study investigated how Ni(II) and hyperglycemic conditions, both singly and in combination, alter monocyte proliferation, mitochondrial activity, inflammatory responses, and differentiation. Results showed that Ni(II) did not affect proliferation, but decreased mitochondrial activity in monocytic‐cells and macrophages under normal conditions. However, hyperglycemic conditions negated the toxicity seen with Ni(II) exposure. Cytokine secretion in response to LPS was variable, with little effect on IL6 secretion, but significantly increased secretion of IL1β at intermediate Ni(II) concentrations. Hyperglycemic conditions did not alter these results significantly. Finally, exposure to eluants from nickel‐based commercial alloys caused enhanced IL1β secretion from PMA‐treated cells. These data suggest that corrosion products from nickel‐containing dental alloys increased Ni(II)‐induced changes in cytokine secretion by monocytes and macrophages. By better defining the effects of Ni(II) at these lower, biomedically relevant concentrations, we improve understanding of the biomedical alloy risk in the context of dental inflammation. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A:2433–2439, 2018.